The geo-economic importance of the Syrian geographical location and its impact on the security of Russian natural gas - Kazem Jasim Al-Husseini, Israa; Fadel Judeh, Hamza (Journal of College of Education, 2021)
Geostrategic studies are considered among the studies that highlight the value of geopolitics, due to the scientific value of these studies for their novelty and their impact on political units, drawing foreign policies and organizing international relations. The Syrian geographic location made it one of the most important geopolitical, economic and military centers in the Middle East, the most vital region in the world. Its location on the eastern bank of the Mediterranean reinforced its geostrategic importance as an advanced coastal gateway to the Asian continent, and this made it an important country for the Russian Federation. The last resort to securing energy sources, ending the constant threat to its markets in the European Union, cutting the way to regional and international energy agendas, through the Syrian geo-economic site, and seeking to implement projects that transport Russian-Iranian gas through Iraq to Syria and then Europe, as the Syrian geostrategic site represents a lifeline for the economy The Russian Federation is highly dependent on gas exports. And an attempt to obstruct any efforts by the United States of America and its allies from the regional